2017
DOI: 10.1016/j.devcel.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3 Complex Is Required for Macrophage Integrin Functions but Is Dispensable for FcR Phagocytosis and In Vivo Motility

Abstract: SUMMARY The Arp2/3 complex nucleates branched actin, forming networks involved in lamellipodial protrusion, phagocytosis and cell adhesion. We derived primary bone marrow macrophages lacking Arp2/3 complex (Arpc2−/−) and directly tested its role in macrophage functions. Despite protrusion and actin assembly defects, Arpc2−/− macrophages competently phagocytose via FcR and chemotax towards CSF and CX3CL1. However, CR3 phagocytosis and fibronectin haptotaxis, both integrin-dependent processes, are disrupted. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
98
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 68 publications
(82 reference statements)
16
98
3
Order By: Relevance
“…Interestingly, similar observations have been made in neutrophils [23] as well as in T lymphocytes, in which mDia1 is required for migration [24,25] while Arp2/3 is not [26]. In agreement with these findings, Arp2/3 activity is mainly required for Integrin-dependent cellular functions of macrophages in vivo, this complex being dispensable for the locomotion of these cells in 3-dimensional environments [27]. It therefore appears that most leukocytes do not rely on branched actin nucleation for migration in confinement, consistent with their migration being independent of adhesion in such complex environment.…”
Section: Through Regulation Of Actin Nucleationsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, similar observations have been made in neutrophils [23] as well as in T lymphocytes, in which mDia1 is required for migration [24,25] while Arp2/3 is not [26]. In agreement with these findings, Arp2/3 activity is mainly required for Integrin-dependent cellular functions of macrophages in vivo, this complex being dispensable for the locomotion of these cells in 3-dimensional environments [27]. It therefore appears that most leukocytes do not rely on branched actin nucleation for migration in confinement, consistent with their migration being independent of adhesion in such complex environment.…”
Section: Through Regulation Of Actin Nucleationsupporting
confidence: 80%
“…Formins might also play a role in the recently described "short-term directional memory of migrating HL-60 neutrophil-like cells" DCs can be fully attributed to impaired Arp2/3 activation has not been shown. Interestingly, recent results obtained on Arp2/3-deficient macrophages suggest that it is only required for these cells to follow immobilized gradient of chemokines, an integrin-dependent process referred to as haptotaxis [27].…”
Section: The Actomyosin Cytoskeleton In Chemical Guidance Of Leukocytesmentioning
confidence: 99%
“…Phagocytosis requires protrusion of the plasma membrane to envelop the target particle, and is well accepted to involve both WASP and WAVE proteins (13,23,67,74). Earlier work already established that Arp2/3 complex -albeit not essential -is crucially contributing to phagocytosis (55,75), while the precise differential contributions of WASP and WRC remained elusive. Accordingly, phagocytosis was found here to be detectable even in the absence of Hem1, although the engulfment of different targets such as bacteria, yeast and opsonized red blood cells or beads was significantly delayed or defective to different degrees as compared to WT and WASP KO macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Freeman and colleagues demonstrated in an elegant piece of work how integrin activation leads to the formation of a diffusion barrier around the opsonized target, which facilitates coordinated particle engulfment during Fc gamma receptor-initiated phagocytosis (87). Interestingly, another recent study using Arp2 knockout cells identified a critical role for Arp2/3 complex-mediated actin assembly in integrin activation, affecting all integrin-dependent processes in macrophages, including migration, adhesion and phagocytosis (75). However, the specific participation of single Arp2/3 complex activators could not yet be delineated, since all Arp2/3-mediated processes were simultaneously switched off.…”
Section: Fc Gamma Receptor (Fc R)-induced Phagocytosis Is Mainly Accomentioning
confidence: 99%
“…It is generally accepted that the F-actin within the phagocytic cup is primarily nucleated by the Arp2/3 complex, although evidence of forminassisted nucleation also exists [50][51][52] . Indeed, staining the actin waves with Arp3 antibody showed discrete puncta in WT macrophages and significant Arp2/3 recruitment to the actin clumps of the dKO macrophages ( Fig.…”
Section: Macrophages Lacking Myo1e and Myo1f Form Disorganized Actin-mentioning
confidence: 99%